High‐Performing Flexible Mg3Bi2 Thin‐Film Thermoelectrics - Boxuan Hu; Xiao‐Lei Shi; Tianyi Cao; Siqi Liu; Min Zhang; Wanyu Lyu; Liangcao Yin; Tuquabo Tesfamichael; Qingfeng Liu; Zhi‐Gang Chen (Advanced Science)
Abstract With the advances in bulk Mg3Bi2, there is increasing interest in pursuing whether Mg3Bi2 can be fabricated into flexible thin films for wearable electronics to expand the practical applications. However, the development of fabrication processes for flexible Mg3Bi2 thin films and the effective enhancement of their thermoelectric performance remain underexplored. Here, magnetron sputtering and ex‐situ annealing techniques is used to fabricate flexible Mg3Bi2 thermoelectric thin films with a power factor of up to 1.59 µW cm−1 K−2 at 60 °C, ranking as the top value among all reported n‐type Mg3Bi2 thin films. Extensive characterizations show that ex‐situ annealing, and optimized sputtering processes allow precise control over film thickness. These techniques ensure high adhesion of the films to various substrates, resulting in excellent flexibility, with <10% performance degradation after 500 bending cycles with a radius of 5 mm. Furthermore, for the first time, flexible thermoelectric devices are fabricated with both p‐type and n‐type Mg3Bi2 legs, which achieve an output power of 0.17 nW and a power density of 1.67 µW cm−2 at a very low temperature difference of 2.5 °C, highlighting the practical application potential of the device.